Handbook of violence risk assessment - Douglas, Kevin S.; Otto, Randy K. (New York, NY : Routledge, 2021)
"The Handbook of Violence Risk Assessment, Second Edition, builds off the previous edition's comprehensive discussion of violence risk assessment instruments with new and revised instruments that enable forensic psychologists to identify and predict the probable behavior of sex predators and violent offenders. Featuring chapters written by the instrument developers themselves, this handbook reviews the most common violence risk assessment instruments - both actuarial and structured professional judgment - used around the world to structure and inform mental health and other professionals' judgments about violence risk. Also included are broader chapters that address matters such as the consideration of psychopathy and how the law shapes violence risk assessment. Newly added chapters cover legal issues, numeric measures, brief and emerging measures, and recently released tests. Already the primary reference for practitioners, researchers, and legal professionals who deal with violent offenders, this second edition's easy-to-access, comprehensive, and current information will make it an indispensable reference for those in the field"--
OCLC-licensed vendor bibliographic record.
Keywords: Violence; Violence -- Forecasting; Risk assessment; Forensic psychiatry; PSYCHOLOGY / Forensic Psychology; PSYCHOLOGY / Mental Health